2013
DOI: 10.1111/mmi.12362
|View full text |Cite
|
Sign up to set email alerts
|

Birth, death and horizontal transfer of the fumonisin biosynthetic gene cluster during the evolutionary diversification of Fusarium

Abstract: SummaryFumonisins are a family of carcinogenic secondary metabolites produced by members of the Fusarium fujikuroi species complex (FFSC) and rare strains of Fusarium oxysporum. In Fusarium, fumonisin biosynthetic genes (FUM) are clustered, and the cluster is uniform in gene organization. Here, sequence analyses indicated that the cluster exists in five different genomic contexts, defining five cluster types. In FUM gene genealogies, evolutionary relationships between fusaria with different cluster types were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 83 publications
(152 reference statements)
6
94
0
Order By: Relevance
“…The co-localization of divergent genetic regions and genes that are absent among related genomes is consistent with what has been reported previously for Fusarium species [4, 14, 59]. Co-localization may suggest that genes were acquired or lost as clusters; multiple gains or losses of gene clusters have been suggested for the secondary metabolite gene cluster responsible for fumonisin biosynthesis in Fusarium [60]. Lineage specific chromosomes and large scale horizontal gene transfer events, such as the transfer of an entire chromosome that have been reported in F. oxysporum , are yet to be reported for members of the F. graminearum species complex [4].…”
Section: Discussionsupporting
confidence: 87%
“…The co-localization of divergent genetic regions and genes that are absent among related genomes is consistent with what has been reported previously for Fusarium species [4, 14, 59]. Co-localization may suggest that genes were acquired or lost as clusters; multiple gains or losses of gene clusters have been suggested for the secondary metabolite gene cluster responsible for fumonisin biosynthesis in Fusarium [60]. Lineage specific chromosomes and large scale horizontal gene transfer events, such as the transfer of an entire chromosome that have been reported in F. oxysporum , are yet to be reported for members of the F. graminearum species complex [4].…”
Section: Discussionsupporting
confidence: 87%
“…This cluster occurs in the same genomic context in F. proliferatum and F. fujikuroi , at another genomic position in F. verticillioides (Proctor et al 2013), but is absent in the genomes of F. mangiferae (supplementary table S1, Supplementary Material online). F. oxysporum O-1819 has an intact cluster, whereas the cluster is absent in 12 other sequenced F. oxysporum strains (Proctor et al 2013). Recently, it has been shown that Aspergillus niger has an intact fumonisin gene cluster (Frisvad et al 2007).…”
Section: Resultsmentioning
confidence: 98%
“…An alternative explanation could be the presence of horizontal gene transfer, already detected in other Geosmithia hydrophobin proteins (Bettini et al 2014), that will better explain the presence of very similar or even identical nucleotide sequences in different species. Such a model of evolution, involving either multiple horizontal transfer events and/or birth-and-death, was recently proposed in Fusarium for the fumonisin biosynthetic gene cluster (Proctor et al 2013).…”
Section: Resultsmentioning
confidence: 99%